International capital movements and human capital growth - Karl-Josef Koch (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
The paper analyses aspects of international capital movements and formation of human capital in a three sector two country growth model. We assume that direct foreign investment from a country with a high level of knowledge goes along with a positive external effect on human capital growth in the capital importing country. Substantially different long run distributions of wealth and human capital can occur in case of small or large externalities. In general it is in the interest of capital exporting and importing countries to encourage foreign direct investment. Although the major positive welfare effect can be observed on the side of the debtor, there still is an incentive in the creditor country to encourage foreign direct investment. International commodity trade allows for a more efficient use of comparative advantages, if the gap of efficiency of labor is smaller. The short and long run distribution of benefits of such strategies is studied analytically and in numerical examples.
Keywords: 330; Auslandsinvestition; Humankapital; Neue Wachstumstheorie; Externer Effekt; Wohlfahrtsanalyse; Theorie